Complicated acute appendicitis in a child with left atrial isomerism: a case report - Faysal Tabbara; Karim Wehby Ataya; Youssef Annous; Kawsar Alamiddine; Ahmad Zaghal (SpringerOpen, 2021)
Abstract Background Heterotaxy syndrome is a rare clinical entity that is characterized by abnormal visceral organ arrangement in the chest and abdomen. Left atrial isomerism is a subcategory of heterotaxy syndrome characterized by the presence of multiple spleens with or without cardiac anomalies. Patients may remain asymptomatic their whole lives until they are diagnosed incidentally. Given that patients with left atrial isomerism might demonstrate atypical presentations of acute intrabdominal pathologies, it is important to keep a high index of suspicion when encountering such cases. Case presentation In this report, we present a case of a 9-year-old boy with a known history of left atrial isomersim who presented with left lower quadrant pain and positive McBurney, psoas, and obturator signs on the left side. A computed tomography scan of the abdomen confirmed the diagnosis of perforated acute appendicitis on the left, which prompted an emergent laparoscopic appendectomy. Conclusion Our case highlights the importance of keeping a high index of suspicion for a heterotaxy syndrome that is complicated by acute appendicitis in pediatric patients presenting with vague abdominal pain. Planning the location of trocar placement in patients with situs anomalies is of paramount importance to avoid technical difficulties in laparoscopic procedures.